An Empirical Study of Factors That Influence the Profitability of South African Retail Firms Listed on The Johannesburg Stock Exchange - Matsoma, Ntomolane Lobisa; Mabandla, Ndonwabile Zimasa; Mamaro, Lenny Phulong (Acta Universitatis Danubius. Œconomica, 2022)
The aim of the study was to investigate empirical factors that influence the profitability of South African retail companies listed on the Johannesburg Stock Exchange (JSE). A positivism, quantitative and deductive research approach was employed to analyse data collected from the Iress database. The sample consisted of 20 JSE-listed retail firms whose information for the period 2011 to 2021 was considered. Retail firms contribute an estimated 3.5% to the gross domestic product (GDP) of the country, but are struggling to maintain their profitability due to limited financial resources. The fixed effect model revealed financial leverage, liquidity and growth to have been positive and to have significantly influenced profitability, whereas firm size and total debt to assets were found to be negative, and were also found to have significantly influenced profitability. The findings contribute to the existing literature and serve to inform future researchers about factors influencing profitability. However, the findings are limited to retail firms in South Africa, and therefore cannot be extended to other sectors of the economy. This suggests the value of conducting further studies in sectors other than retail. These results could be useful as a point of reference for future researchers, managers, and investors.